Ectopic Terpene Synthase Expression Enhances Sesquiterpene Emission in Nicotiana attenuata without Altering Defense or Development of Transgenic Plants or Neighbors . Issue 2 (3rd September 2014) - Schuman, Meredith C.; Palmer-Young, Evan C.; Schmidt, Axel; Gershenzon, Jonathan; Baldwin, Ian T.
Abstract : Plants expressing two sesquiterpene synthases emitted increased quantities of target volatiles without changes to other volatiles, defense, growth, or yield in transformants or neighboring plants . Abstract: Sesquiterpenoids, with approximately 5, 000 structures, are the most diverse class of plant volatiles with manifold hypothesized functions in defense, stress tolerance, and signaling between and within plants. These hypotheses have often been tested by transforming plants with sesquiterpene synthases expressed behind the constitutively active 35S promoter, which may have physiological costs measured as inhibited growth and reduced reproduction or may require augmentation of substrate pools to achieve enhanced emission, complicating the interpretation of data from affected transgenic lines. Here, we expressed maize ( Zea mays ) terpene synthase10 ( ZmTPS10 ), which produces ( E )-α-bergamotene and ( E )-β-farnesene, or a point mutant ZmTPS10M, which produces primarily ( E )-β-farnesene, under control of the 35S promoter in the ecological model plant Nicotiana attenuata . Transgenic N. attenuata plants had specifically enhanced emission of target sesquiterpene(s) with no changes detected in their emission of any other volatiles. Treatment with herbivore or jasmonate elicitors induces emission of ( E )-α-bergamotene in wild-type plants and also tended to increase emission of ( E )-α-bergamotene and ( E )-β-farnesene in transgenics. However, transgenics did not differ from the wild type in defense signaling or chemistry and did not alter defense chemistry in neighboring wild-type plants. These data are inconsistent with within-plant and between-plant signaling functions of ( E )-β-farnesene and ( E )-α-bergamotene in N. attenuata . Ectopic sesquiterpene emission was apparently not costly for transgenics, which were similar to wild-type plants in their growth and reproduction, even when forced to compete for common resources. These transgenics would be well suited for field experiments to investigate indirect ecological effects of sesquiterpenes for a wild plant in its native habitat.